Occurrence of the antidiabetic drug Metformin and its ultimate transformation product Guanylurea in several compartments of the aquatic cycle - Trautwein, Christoph; Berset, Jean-Daniel; Wolschke, Hendrik; Kümmerer, Klaus (Environment international, 2014)
In 2030, the World Health Organization estimates that more than 350million people will be diagnosed with diabetes. Consequently, Metformin – the biguanide drug of choice orally administered for diabetes type II – is anticipated to see a spike in production. Unlike many pharmaceutical drugs, Metformin (Met) is not metabolized by humans but passes through the body unchanged. Entering aquatic compartments, such as in sewage, it can be bacterially transformed to the ultimate transformation product Guanylurea (Gua). Sampling over one week (n=5) from a Southern German sewage treatment plant revealed very high average (AV) concentrations in influent (AVMet=111,800ng/L, AVGua=1300ng/L) and effluent samples (AVMet=4800ng/L, AVGua=44,000ng/L). To provide a more complete picture of the distribution and potential persistence of these compounds in the German water cycle, a new, efficient and highly sensitive liquid chromatography mass spectrometric method with direct injection was used for the measurement of Metformin and Guanylurea in drinking, surface, sewage and seawater. Limits of quantification (LOQ) ranging from 2–10ng/L allowed the detection of Metformin and Guanylurea in different locations such as: Lake Constance (n=11: AVMet=102ng/L, AVGua=16ng/L), river Elbe (n=12: AVMet=472ng/L, AVGua=9ng/L), river Weser (n=6: AVMet=349ng/L, AVGua=137ng/L) and for the first time in marine North Sea water (n=14: AVMet=13ng/L, AVGua=11ng/L). Based on daily water discharges, Metformin loads of 15.2kg/d (Elbe) and 6.4kg/d (Weser) into the North Sea were calculated. Lake Constance is used to abstract potable water which is further purified to be used as drinking water. A first screening of two tap water samples contained 2ng/L and 61ng/L of Metformin, respectively. The results of this study suggest that Metformin and Guanylurea could be distributed over a large fraction of the world's potable water sources and oceans. With no natural degradation processes, these compounds can be easily reintroduced to humans as they enter the food chain. •New HPLC–MS/MS method for Metformin and Guanylurea with minimal LOQs•First detection of both compounds in German rivers Elbe and Weser•First detection in marine environments until 200km North Sea offshore•First detection in multinational Lake Constance and derived drinking water•Absence proof of any efficient degradation process suggests ubiquitous distribution.